Editorial: We Own Ourselves: Métis-specific Education - Delgado, Lucy (Canadian Journal of Education/Revue canadienne de l'éducation, 2025)
Since the publication of the Truth and Reconciliation Commission’s summary report and 94 calls to action, educational bodies across Canada have taken seriously the call to advance reconciliation. Provincial curricula have been re-written to attempt to better include the stories of Indigenous peoples’ experiences with treaty, residential schools, and settler colonial systems and abuses more broadly. Teacher education programs have included or increased their focus on Indigenous content requirements for all teachers. Some post-secondary institutions have moved to require Indigenous content courses for all students. Within this broad move towards Indigenization, however, the experiences of Métis people are often lost.